You are entitled to access the full text of this document Enhancing sustainable performance through circular economy: The mediating roles of green supply chain and process innovation , - Sultan Alateeg; Sura Alayed (Journal of Project Management)
This study examines the relationships between circular economy capability, green supply chain, green process innovation, and sustainable performance in the manufacturing sector of Saudi Arabia. As the country transitions toward its Vision 2030 goals, which emphasize sustainability and economic diversification, the manufacturing sector plays a critical role in adopting circular economy principles and green practices to reduce environmental impact and enhance resource efficiency. Using a cross-sectional research design, data were collected from managerial-level employees through a structured questionnaire. Data analysis was conducted using structural equation modeling (SEM) to examine the hypothesized relationships. The findings reveal that circular economy capability significantly drives green supply chain and green process innovation, which in turn enhance sustainable performance. The study also identifies green supply chain and green process innovation as critical mediators in the relationship between circular economy capability and sustainable performance. The results highlight the importance of integrating circular economy principles with green practices to achieve sustainability goals. It provides actionable insights for organizations to enhance their sustainability efforts, such as investing in resource efficiency, adopting green supply chain practices, and fostering process innovation.